EFEKTIVITAS PERENDAMAN PUPUK NPK TERHADAP LAJU PERTUMBUHAN DAN PRODUKTIVITAS RUMPUT LAUT EUCHEUMA COTTONII DI TELUK SEREWE: Effectiveness Of Npk Fertilizer Fertilizers On Growth And Productivity Seaweed Eucheuma cottonii In Teluk Serewe - Zaitun, Nurul; Soraya, Indah; Rahmawati, Aryani (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2025)
Eucheuma cottonii is one of the marine commodities with high economic value and has an increasing demand trend, so it needs an increase in production.Increased production can also be done by immersion with fertilizer.The purpose of this research is to test the effectiveness of the use of NPK fertilizer on the growth of E. cottonii.This study was conducted for 42 days in Serewe Bay.The research method used was census method, using regression consisting of 4 treatments and 3 replications.Treatment 1 (18 hours immersion), treatment 2 (12 hours), treatment 3 (6 hours) and treatment 4 as control treatment.The results showed that the average of absolute growth rate, and the highest daily growth rate was found in treatment 4 (control), that is 157,5 gram and 0,24 g / day and the lowest was in treatment 3 with value 57,812 gram and 0 , 24 g / day.The conclusion of this research is the use of NPK fertilizer with different soaking period on seaweed cultivation has not been able to produce ideal growth